Modeling a continuous multistage liquid phase cyclohexane oxidation reactor network - Bhattacharya, Arijit (Chemical Engineering and Processing, 2005)
A model is presented for a continuous multistage liquid phase cyclohexane oxidation reactors-in-series network, which uses, unlike previous efforts, a closed form rate model derived on the basis of the well-known free-radical kinetic mechanism of the oxidation reaction leading to a more generalized representation of the oxygen dependence of the rate. The model calculates the required transport and hydrodynamic parameters by one of the best available set of correlations shown earlier to be successfully used in cyclohexane oxidation in a well-designed laboratory reactor. Process sensitivities with regard to variables such as air rate, residence time, head pressure, inlet air composition and sparger configuration have been predicted. Some of these trends compared very well with the limited published experimental data in a three (351) agitated and sparged tank-in-series reactor system, thus partially validating the model. The model has highlighted a fairly generalized way of correlating performance data from a given reactor, namely in terms of a yield-conversion characteristic which can change depending on the mass transfer efficiency and the effective kinetics. Hence, it can aid in plant monitoring and optimization. It has also been shown how to use the same as an aid in preliminary scale-up studies based on laboratory or pilot plant reactor performance data. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: continuous multistage reactor; Cyclohexane; Liquid phase oxidation

Chromium-containing small pore mesoporous silicas: synthesis, characterization and catalytic behavior in the liquid phase oxidation of cyclohexane - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Applied Catalysis A-General, 2007)
Organic-inorganic hybrid mesoporous silica materials containing chromium and various organo trialkoxysilanes (chloropropyl, vinyl, methyl) were prepared by the co-condensation method, in the presence of cetyl trimethyl ammonium surfactants. The hybrid material, containing chromium, retains one X-ray diffractogram (XRD) peak up to a molar ratio of 1: 1 between tetra ethyl orthosilicate (TEOS) and organosilane in the synthesis gel. Small pore mesoporous chromium-silica samples can be prepared from the large pore hybrid mesoporous chromium samples by calcination. By this method, the pore size of the material can be tailored into the supermicroporous region, without changing the chain length of the surfactant used in the assembly process, as judged from the XRD and N-2 sorption isotherms. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups, such that the chloro propyl and vinyl pendant mesoporous material show more pore size shrinkage than the smaller methyl pendant units. Because of the tailorable pore size and with better textural characteristics, the chromium samples show better catalytic activity in the aerial oxidation reaction of cyclohexane than the conventional chromium-containing mesoporous material, like Cr-MCM-41, under a solvent free system. Among the porous chromium catalysts, the samples prepared using chloro propyl silane show higher cyclohexane conversion and cyclohexanone selectivity and behave as a true heterogeneous catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chromium; Cyclohexane; Oxidation; small pore silicas

One step synthesis of chromium-containing periodic mesoporous organosilicas and their catalytic activity in the oxidation of cyclohexane - Shylesh, S.; Srilakshmi, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2007)
Chromium-containing ethane-bridged hybrid mesoporous materials (Cr-PMO) with uniform hexagonal arrangement were synthesized by two different synthesis routes using 1,2-bis(triethoxysilyl)ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts (ATMA) as surfactants. Powder X-ray diffraction, TEM, N-2 adsorption-desorption, FT-IR, in situ FT-Raman, UV-ViS, XPS, Si-29 MAS NMR and C-13 CP MAS NMR were used to probe the mesoporous structure and the nature of chromium sites in the hybrid catalyst matrix. PXRD, TEM and N-2 adsorption-desorption analysis showed that the original hexagonal structure of the materials is maintained after chromium substitution, while FT-Raman, UV-Vis and XPS analysis showed that chromium atoms exist in a highly dispersed state. The catalytic performance of the chromium-containing hybrid samples was tested in the liquid-phase oxidation of cyclohexane with aqueous hydrogen peroxide (H2O2) and non-aqueous tert-butylhydroperoxide (TBHP) as oxidants. The hybrid materials exhibited better catalytic activities and were more stable than the conventional Cr-MCM-41 catalyst. The higher catalytic activity of the new chromium-containing molecular sieves is attributed to the improved hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of cyclohexane to the active framework chromium sites. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Cr-MCM-41; Cr-PMO; Cyclohexane; hybrid mesoporous materials; Oxidation

Bridging the gap between micropores and mesopores by the controlled transformation of bifunctional periodic mesoporous silicas - Shylesh, S.; Srilakshini, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2008)
Novel bifunctional periodic mesoporous silicas having high content of organic groups in the pore channels and chromium in the frame wall has been synthesized by direct co-condensation method, using organo trialkoxysilanes (chloro propyl, vinyl, methyl), chromium nitrate and tetraethyl orthosilicate, in presence of cetyltrimethyl ammonium surfactants. The obtained materials show one main peak in the XRD patterns up to a molar ratio of 1: 1 between TEOS and organosilane in the synthesis gel and N-2 adsorption-desorption analysis shows that the mesopore structure remains intact after the surfactant removal process. Among the organosilanes, chloro propyl and vinyl pendant chromium samples shows a shift in the main peak to higher 2-theta values with a corresponding decrease in pore volume and pore diameter, with the percentage of organosilane functionalization. Small-pore silicas and chromium silicas can be prepared from the large pore mesoporous MCM-41, by effectively removing the organic groups by calcination. By this method, the pore size of the material can be tailored into the super-microporous region, without changing the chain length of the surfactant used in the assembly process. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups that the chloro propyl and vinyl pendant mesoporous materials show the maximum pore size shrinkage than the small chain length methyl units. Because of the tailorable pore size and with better textural characteristics, chromium-silica materials find applications in the field of shape selective heterogeneous catalysis, as demonstrated in the oxidation reaction of cyclohexane, than the conventional metal-containing mesoporous materials. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: bifunctional silicas; chromium; Cyclohexane; MCM-41; Oxidation

Catalytic aerobic oxidation of cyclohexane and ethyl benzene over chromium-containing mesoporous organosilicas - Singh, A. P.; Torita, N.; Shylesh, S.; Iwasa, N.; Arai, M. (Catalysis Letters, 2009)
Chromium-containing ethane-bridged hybrid periodic mesoporous organosilicas (Cr-PMO) were synthesized using 1,2-bis(triethoxysilyl) ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts as surfactants by two different synthesis routes. PXRD and N(2) adsorption-desorption analysis shows that the original structure of the materials is maintained after chromium substitution while spectroscopic study proves the incorporation of chromium in the frame wall positions and show the existence of Cr(2)O(3) species in the mixed silica source (BTEE-TEOS) synthesized chromium samples. The catalytic activity of the newly developed chromium samples was evaluated in the liquid phase oxidation of cyclohexane and ethylbenzene using air as an oxidant. Further, the Cr-PMO samples exhibited better cyclohexane conversion and cyclohexanone selectivity than the conventional Cr-MCM-41 and other metal-containing MCM-41 samples. The exceptional activity of the new chromium-containing molecular sieves is attributed to the hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of substrate to the active framework chromium sites.
Keywords: Cr-MCM-41; Cyclohexane; Ethyl benzene; Organosilicas; Oxidation

Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2010)
Nanoscale Fe-Pd bimetallic particles were synthesized and used for degradation of lindane (gamma-hexachlorocyclohexane) in aqueous solution. Batch studies showed that 5 mg/Lof lindane was completely dechlorinated within 5 min at a catalyst loading of 0.5 g/L and the degradation process followed first-order kinetics. GC-MS analysis in corroboration with GC-ECD results showed the presence of cyclohexane as the final degradation product. The proposed mechanism for the reductive dechlorination of lindane involves Fe corrosion-induced hydrogen atom transfer from the Pd Surface. The enhanced degradation efficiency of Fe-Pd nanoparticles is attributed to: (1) high specific surface area of the nanoscale metal particles (60 m(2)/g), manyfold greater that of commercial grade micro- or milli-scale iron particles (similar to 1.6 m(2)/g); and, (2) increased catalytic reactivity due to the presence of I'd on the Surface. Recycling and column studies showed that these nanoparticles exhibit efficient and sustained catalytic activity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bimetallic; Cyclohexane; Degradation; kinetics; Lindane; Nanoparticles